Effects of Natural Products on Bacterial Communication and Network-Quorum Sensing. (27th May 2020) - Yang, Min; Meng, Fanying; Gu, Wen; Li, Fengjiao; Tao, Yating; Zhang, Zhengyang; Zhang, Fan; Yang, Xingxin; Li, Jingping; Yu, Jie
Abstract : Quorum sensing (QS) has emerged as a research hotspot in microbiology and medicine. QS is a regulatory cell communication system used by bacterial flora to signal to the external environment. QS influences bacterial growth, proliferation, biofilm formation, virulence factor production, antibiotic synthesis, and environmental adaptation. Through the QS system, natural products can regulate the growth of harmful bacteria and enhance the growth of beneficial bacteria, thereby improving human health. Herein, we review advances in the discovery of natural products that regulate bacterial QS systems.